Palliative care nurses’ perspectives on managing a disaster situation: a focus group study - Marco Paulo da Silva Mendonça; Milene Isabel Costa Mendonça Lima; Diana Tavares Costa Ponte; Adélia Lúcia Franco Costa; André Filipe Rocha Rego Oliveira; Carla Marisa Salgadinho Melo; Cristina Verónica Macedo Couto; Tamára Oliveira Martins; Ana Sofia Carreiro Jorge (BMC Nursing)
Abstract Background Nurses who provide palliative care play a fundamental role in delivering and managing care for victims of disasters and public health emergencies. However, in these contexts, the role of palliative care remains a low priority. This study aimed to explore the perspectives of specialist nurses from a hospital palliative care unit regarding the management of a large-scale fire, which led to the evacuation and complete deactivation of a central hospital. Methods This qualitative, descriptive, and exploratory study used content analysis of data collected through a focus group. The focus group consisted of specialist nurses with advanced training in palliative care from a hospital palliative care unit who had experienced a disaster situation. Results The participants identified six domains of nursing expertise essential for managing the crisis: preparation and planning, communication, safety and protection, intervention, assessment and recovery, and law and ethics. The identification of needs and challenges related to nursing expertise in palliative care was also considered crucial for a more effective response in disaster contexts. Conclusions The findings highlighted that the expertise of specialist palliative care nurses is vital in responding to disasters, as they play a key role in alleviating the suffering of individuals affected by such events. Teamwork, leadership, and the training of nurses in palliative care were identified as critical elements for the effective management of disaster situations. The integration and contribution of palliative care nurses in the development of policies, planning, and disaster response are essential for future situations, regardless of the context.